Comparative morphological and histological study of the pecten oculi in two species of Iraqi birds (Falco tinnunculus L. and Streptopelia decaocto F.) - Baghdad Science Journal (مجلة بغداد للعلوم)
Study showed structure of pecten oculi in the Kestrel Falco tinnunculus L.was Pleated type and consisted of 17 folds which were thick. While in the Collared Dove Streptopelia decaocto F. was Vaned type and consisted of 13 folds and it described thin. The illustrated histological study of pecten oculi folds in the Kestrel and the Collared Dove was composed of large number of capillaries, large blood vessels and pigment cells which were few in Kestrel compare with the Collared Dove. The bridge in the Kestrel and the Collared Dove pecten oculi was consisted of connective tissue, many pigment cells, and contains on little capillaries and it linked the membrane to the internal limiting membrane of the retina in the Kestrel. Key words: birds, pecten oculi, morphology, histology